2010
DOI: 10.1021/tx100047d
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Lipid Peroxidation-Induced DNA Adducts Caused by 4-Oxo-2(E)-nonenal and 4-Oxo-2(E)-hexenal in Human Autopsy Tissues

Abstract: DNA adducts are produced both exogenously and endogenously via exposure to various DNA-damaging agents. Two lipid peroxidation (LPO) products, 4-oxo-2(E)-nonenal (4-ONE) and 4-oxo-2(E)-hexenal (4-OHE), induce substituted etheno-DNA adducts in cells and chemically treated animals, but the adduct levels in humans have never been reported. It is important to investigate the occurrence of 4-ONE- and 4-OHE-derived DNA adducts in humans to further understand their potential impact on human health. In this study, we … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
64
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 71 publications
(65 citation statements)
references
References 32 publications
1
64
0
Order By: Relevance
“…One recent study looked at several human tissues by LC-MS/MS for Hε-DNA-adducts. Such adducts were found among several tissue types, including colon, heart, kidney, lung, pancreas, and small intestine [109]. The authors of this study also examined the levels of 8-oxo-dGuo, the most commonly found adduct, and found that there was no correlation to the levels of 8-oxo-dGuo compared to HεdCyd [109].…”
Section: Cox-2-mediated Dna Damagementioning
confidence: 99%
“…One recent study looked at several human tissues by LC-MS/MS for Hε-DNA-adducts. Such adducts were found among several tissue types, including colon, heart, kidney, lung, pancreas, and small intestine [109]. The authors of this study also examined the levels of 8-oxo-dGuo, the most commonly found adduct, and found that there was no correlation to the levels of 8-oxo-dGuo compared to HεdCyd [109].…”
Section: Cox-2-mediated Dna Damagementioning
confidence: 99%
“…This “pseudo-CNL” methodology was used to characterize lipid peroxidation DNA adducts in human tissues. 2729 Numerous signals were detected; however, it is not known whether these analytes are DNA adducts or simply other compounds in the DNA digest matrix that lose 116 Da upon CID. The Turesky laboratory laid the groundwork for the linear ion trap (LIT)-MS based adductomics method.…”
Section: Introductionmentioning
confidence: 99%
“…The importance of lipid peroxidation-derived DNA damage in inflammatory diseases has been implied [20], and, in fact, levels of lipid peroxidation and oxidised low-density lipoprotein are highly expressed in RA patients, while a positive association between RA disease activity and lipid peroxidation has been reported [10, 15, 21]. Polyunsaturated fatty acids (PUFAs) exerting oxidative stress have been found to cause a series of α , β -unsaturated aldehydes such as acrolein, crotonaldehyde, and malondialdehyde to form lipid peroxyl radicals, which are highly DNA- and protein-reactive [7, 10, 14, 22, 23]. H ε dC has an exocyclic ring and a bulky side chain formed by deoxycytidine reacting with 4-ONE and may lead to alterations in mitochondrial function [7, 14, 2225].…”
Section: Discussionmentioning
confidence: 99%
“…DNA damage induced by exposure to ionizing radiation, ultraviolet light, and exogenous or endogenous chemical mutagens causes DNA strand breakages, which are thought to be mutagenic, carcinogenic, and aging factors [2]. Additionally as new DNA damage, lipid peroxidation-derived DNA adducts have been recently reported in human [7], and lipid peroxidation has been also considered as a factor of the pathogenesis or the local inflammatory response of RA [4, 8–10]. Representative DNA adducts are 8-oxo-dG, 1,N 6 -etheno-2′-deoxyadenosine ( ε dA), and heptanone-etheno-2′-deoxycytidine (H ε dC); the latter two of which are direct reactive oxygen species- (ROS-) derived and lipid peroxidation-derived adducts.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation